Evolved UTRA - physical layer overview - Tanno, M.; Kishiyama, Y.; Miki, N.; Higuchi, K.; Sawahashi, M. (2007 IEEE 8th Workshop on Signal Processing Advances in Wireless Communications, 2007)
This paper presents the physical layer features and structures, along with the NTT DoCoMo's proposals on solutions for the Evolved UTRA. After completion of study item investigations, outlines for physical channel structures were determined. The proposals for the orthogonal reference signal structures, multiplexing of the synchronization signal and broadcast channel appropriate to scalable multiple transmission bandwidths, the hierarchical synchronization signal structure, the downlink Layer 1 (L1) /Layer 2 (L2) control channel structure, and block-wise resource block-level distributed transmission for the shared data channel in the downlink are described. Other proposals such as purpose grouping for the random access channel in the uplink, the uplink L1/L2 control channel structure, and a link adaptation scheme for the shared data channel are also presented.